ELECTIVE COURSE DEVELOPMENT AND EVALUATION FOR THIRD-YEAR PHARMACY STUDENTS ON PHARMACY HEALTH COACHING IN INDONESIA - Alexxander, Alexxander; Puspitasari, Ika; Kristina, Susi Ari; Pratiwi, Restu Dwi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
To describe our experiences in developing an elective course for third-year pharmacy students on pharmacy health coaching, as well as to evaluate its effects on students' attitudes, knowledge, and skills. The 3 Co-TEAM models consist of 18 hours of course modules. A multiple-choice and essay quiz was used to assess students' mastery of essential abilities pre and post elective courses. After the last teaching session, students' self-perceived attitude, knowledge, and skills were evaluated through a voluntary survey. Of the 60 students in the third year, only 7 students are willing to voluntarily take the elective course. The development of the curriculum resulted in a course of 3 modules, the duration of each course was 2 hours. Results showed that there was a significant improvement in knowledge overall mean score before and after the course (38.79, SD=7.11 and 81.21, SD=5.34, respectively, p<0.05). The overall mean composite score in the student’s perceived attitudes, knowledge, and skills was increased by 48.35%, 96.43%, 51.91%, respectively; p<0.05. This elective course has proven to be a successful way of educating pharmacy students. We advocate the incorporation of this style of education into the learning process to improve student's learning experiences while still supporting traditional healthcare learning.